Needlistick injury: a review of twelve theses among healthcare personnel in Malaysia - Noor Hassim Ismail; K.G. Rampal (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2009)
Aims : The review was to determine the prevalence of needlestick injury especially among health care personnel and to determine the score of knowledge and compliance to the Standard Universal Precaution. Method : Twelve theses were reviewed from year 1996 to 2007 of Master in Community Health Science, Master in Community Health and Postgraduate Diploma in Occupational Health of Community Health Department Universiti Kebangsaan Malaysia Medical Center involving of 1645 respondents of health care personnel, support staff and student of nursing and medical. Eleven studies were cross sectional design and only one study was retrospective. Results : Respondents were dominated by female (74.6%) and Malay ethnicity (65%), as young as 19 years old to 56 years old of age. Majority had received Hepatitis B vaccination (79.4%) but only 37.1% had completed the 3 doses regime. The incidence of episodes of needle stick injury among health care personnel was double (53.7%) compared to final year medical students (20.9%). Needle stick injuries did not occur at random as there were a few health care personnel injured repeatedly. Those who had higher mean or median score for compliance to Standard Universal Precaution were non case of needlestick injury. Work practices had been highlighted in few studies of being risk factors for needlestick injury such as blood withdrawing related activities. Other risk factors were job category, predictive factor for compliance to Standard Universal Precaution, risk perception and training. Conclusion : Even though the review could not extrapolated to general population of healthcare personnel but it gave some illustrated pictures to what had happened in small clustered locations. Episodes of needle stick injury was 53.7% for past 12 years, it was double in comparison to final year medical students in year 2001. 13.2% were injured repeatedly. The score of knowledge was more the 50% of range but compliance to Standard Precaution made differences in being cases or non cases among respondents. The seroconversion status till date was unknown.